Case report: Salmonella enterica serovar Paratyphi B infection in a febrile Ill child during enhanced passive surveillance in an urban slum in Mirpur, Dhaka - Khanam, F; Rajib, NH; Tonks, S; Zaman, K; Pollard, AJ; Clemens, JD; Qadri, F; Strataa Study Team (American Society of Tropical Medicine and Hygiene, 2020)
Paratyphoid fever is one of the major causes of morbidity of febrile illnesses in endemic regions. We report a case of high-grade fever in an infant who was positive for Salmonella enterica serovar Paratyphi B (S. Paratyphi B) both in blood and stool cultures. The baby was enrolled in the passive surveillance of multicenter, multicomponent epidemiological study of enteric fever (Strategic Typhoid alliance across Africa and Asia; STRATAA) conducted in a population of 110,000 residents over 2 years in an urban slum, Dhaka, Bangladesh. This is the only patient who was positive for S. Paratyphi B in blood and stool among more than 6,000 febrile ill patients enrolled in the passive surveillance. The report shows the significance of surveillance to identify changes in the epidemiology of enteric fever.